Avaliação da qualidade de vida da pessoa com úlcera venosa no município de Três Lagoas/Mato Grosso do Sul - Jaqueline Goulart de Oliveira (2021)
Quality of life (QOL) is an important measurable data for health systems, reflecting the individual's position when experiencing a pathology, the damages and treatments resulting from it. Its measurement occurs through self-assessment questionnaires of health status, which investigate the main dimensions that can impact the individual's life. Another measure of similar relevance for health is the functional capacity (FC), a result of the interaction between the individual's physical, mental and psychosocial capacities and the environment in which he lives, whose decline can be observed in the presence of chronic diseases. Its investigation is carried out through self-report instruments, whose measurements can reveal the difficulties in carrying out various specific daily activities. Both dimensions, QOL and FC, can be compromised in people affected by venous ulcers (VU). The objective of this research was to evaluate the QOL of people with venous ulcers assisted in the municipal public health network of Três Lagoas, state of Mato Grosso do Sul. This is an observational, cross-sectional study, carried out with 57 people. Data were collected from August to December 2020, using three questionnaires: one to assess sociodemographic, health and treatment information; the Freiburg Life Quality Assessment - Wound (FLQA-wk), to assess QOL, and the Late-Life Function and Disability Instrument (LLFDI), applied only to the elderly, to assess FC. For data analysis, Mann Whitney, Kruskal Wallis and Spearman correlation tests were used. The results showed, through the QOL scores, greater impairment in the satisfaction, physical symptoms and daily life domains, and better assessment in the psychological well-being domain. By correlating or comparing QOL with sociodemographic variables, statistical significance was obtained between the variables: gender and the treatment domain; age and the physical symptoms and psychological well-being domain; marital status and the satisfaction domain; diabetes mellitus and the physical symptoms domain; hypertension and the physical symptoms, daily life and psychological well-being domains; time of existence of the lesion and the social life domain; having someone to help with the dressing at home and the treatment domain. The FC scores in elderly people revealed greater impairment in the social, personal and advanced lower limbs domains, for those who use mobility devices or not. The correlation between QOL and FC showed greater impairment in the physical symptoms, daily life, social life and psychological well-being domains, with greater disability in the personal, instrumental and management domains; greater impairment in the basic function of the lower limbs, with a poor assessment in social life; greater disability in the personal and instrumental domains, and impaired assessment in the visual analogue scales, general health status, wound status and quality of life in general. The results of this research reveal that there were indications that living with VU damages the individual's QOL and FC. Keywords: Varicose ulcer. Quality of life. Therapeutics. Public Health Nursing. Epidemiologic Factors.